2013
DOI: 10.1002/pola.26663
|View full text |Cite
|
Sign up to set email alerts
|

Coloring–decoloring behavior of fluoroalkyl end‐capped 2‐acrylamido‐2‐methylpropanesulfonic acid oligomer/acetone composite in methanol

Abstract: A reddish‐brown fluoroalkyl end‐capped 2‐acrylamido‐2‐methylpropanesulfonic acid (AMPS) oligomer/acetone composite was prepared by heating the white oligomer powder with acetone at 80 °C for 3 h. The color was not observed in the corresponding non‐fluorinated AMPS oligomer/acetone composite, which was prepared under similar conditions. The coloring was probably caused by the formation of acetone polyaldol condensation products in the fluorinated oligomeric gel network cores. The colored RF‐(AMPS)n‐RF/acetone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…[37] In addition, the retro-polyaldol condensation of acetone was also found to decolor the solution after 1 day at room temperature. [37] Here, we report that R F -(AMPS) n -R F oligomer can interact with not only acetone but also aromatic ketones such as 4′-methoxyacetophenone (MAP) to give the homoaldol condensation product under mild conditions, although the corresponding non-fluorinated AMPS oligomer and sulfuric acid cannot afford the corresponding product at all under similar conditions. EXPERIMENTAL Measurements 1 H NMR spectra were recorded using a JEOL JNM-ECA 500 (500 MHz) FT NMR SYSTEM (Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…[37] In addition, the retro-polyaldol condensation of acetone was also found to decolor the solution after 1 day at room temperature. [37] Here, we report that R F -(AMPS) n -R F oligomer can interact with not only acetone but also aromatic ketones such as 4′-methoxyacetophenone (MAP) to give the homoaldol condensation product under mild conditions, although the corresponding non-fluorinated AMPS oligomer and sulfuric acid cannot afford the corresponding product at all under similar conditions. EXPERIMENTAL Measurements 1 H NMR spectra were recorded using a JEOL JNM-ECA 500 (500 MHz) FT NMR SYSTEM (Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is particularly desirable to develop fluoroalkyl end‐capped AMPS oligomeric nanoparticles for encapsulating not only metal nanoparticles but also organic guest molecules. In fact, we have very recently succeeded in the encapsulation of acetone in fluoroalkyl end‐capped AMPS oligomeric aggregate cores to give the reddish‐brown fluorinated AMPS oligomer [R F ‐(AMPS) n ‐R F ]/acetone composite . It has been demonstrated that the color can arise from acetone encapsulated in the fluorinated AMPS oligomeric gel network cores forming acetone polyaldol condensation products .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have hitherto comprehensively studied on the preparation and applications of fluoroalkylated polymers, especially, ABA triblock-type fluoroalkyl end-capped oligomers [R F -(M) n -R F : R F = fluoroalkyl groups, M=radical polymerizable monomer], and these fluorinated oligomers can exhibit a wide variety of unique properties such as high solubility, surface-active property, and nanometer size-controlled molecular aggregates, which cannot be achieved by the corresponding non-fluorinated and randomly fluoroalkylated ones [33][34][35][36][37]. The self-assembled fluorinated oligomeric aggregates formed by these fluoroalkyl end-capped oligomers can provide suitable host moieties to interact with numerous guest molecules such as fullerene, carbon nanotubes, gold, silver and copper nanoparticles, and organic dyes, affording the corresponding fluorinated aggregates/guest molecules nanocomposites [38][39][40][41][42][43][44][45][46][47]. In addition, preparation of poly(vinylidene fluoride) copolymers/silica nanocomposites has been reported including their unique properties [48][49][50].…”
Section: Introductionmentioning
confidence: 99%